Theoretical considerations on the concept of leadership and its application in educational research - Navarro-Corona, Claudia (2015)
For decades, leadership has been studied from numerous perspectives and in different areas of knowledge; however, the many approaches and the great number of publications, far from contributing to the discussion, have prevented a consensus.  Despite its lack of clarity, the term continues to gain importance in the field of educational research.  Based on the review of 40 publications, including five meta-analyses, this paper seeks to answer the following questions: How is leadership defined? How has the concept developed in the field of education and in other fields? What insights derived from the review of the literature are relevant to the work of school principals?  This article supports the prevailing lines of research on leadership and provides and integrative view of the three main approaches.  Leadership is considered a form of social order that emerges from the match between the characteristics of the leader and the needs of a group in a specific situation.  It concludes that leadership is a fragile structure that is vulnerable and corruptible when it is established as a permanent working order.  If there is clarity as to the origin of leadership as a phenomenon, the expectations about the performance of school principals will be defined.